An outbreak of photosensitization (jacapo) in sheep in Junin, Peru - Choez A., Katherine (2018)
An outbreak of photosensitization (locally called jacapo) in the district of Carhuamayo, department of Junin, Peru, that affected 10 animals of a flock of 150 Corriedale sheep is described. The flock was reared under an extensive breeding system. The affected animals presented ocular and cutaneous lesions in the region of the head with different degrees of severity. The jacapo was described more than 20 years ago as a sporadic disease in Peru; however, because of climate change and the deterioration of the ozone layer, it is becoming an emerging disease that is affecting sheep flocks in the central highlands of the country.